2012
DOI: 10.1111/j.1745-6606.2011.01222.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining Consumers' Perceptions of the Health Benefits of Products with Fiber Claims

Abstract: Many foods, including margarines and sugary cereals that were once viewed as unhealthy, are being reformulated and repositioned as healthier. A number of companies have launched new products touting fiber. Critics express concern that the increased interest in fiber as a marketing claim is not necessarily a good thing for consumers because many companies are using isolated fiber that does not have all the health benefits as naturally occurring fiber. This research examines whether consumers understand informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…The odds of obesity are reduced in the prudent dietary pattern, since it is rich in fruits and vegetables, which contain fiber (Burton‐Freeman, 2000; Glore, Van Treeck, Knehans, & Guild, 1994; Zank & Kemp, 2012). In addition, chewing fiber requires more time than normal foods (Heaton, 1973) and it absorbs more water, creates a viscous gel that increases stomach distention (Howarth, Saltzman, & Roberts, 2001), provides low energy, and slows down the gastric emptying (Ruhee & Suzuki, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The odds of obesity are reduced in the prudent dietary pattern, since it is rich in fruits and vegetables, which contain fiber (Burton‐Freeman, 2000; Glore, Van Treeck, Knehans, & Guild, 1994; Zank & Kemp, 2012). In addition, chewing fiber requires more time than normal foods (Heaton, 1973) and it absorbs more water, creates a viscous gel that increases stomach distention (Howarth, Saltzman, & Roberts, 2001), provides low energy, and slows down the gastric emptying (Ruhee & Suzuki, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, even though results of studies identified tobacco as a health hazard in the popular press in the 1950s, the change in aggregate consumer behavior has been a result of a combination of more specific product warning information, stiff retail price increases, severe restriction of availability and broad reductions in promotional activities. Clearly, simple provisions of warning information are not adequate to reduce consumption of some products (Capella, Taylor, and Kees 2012), encourage beneficial consumption of other products (Zank and Kemp 2012) or allow consumers to withdraw from some markets (Garrison et al 2012; Labrecque et al 2012).…”
Section: Efforts To Improve Product Literacymentioning
confidence: 99%
“…Zank and Kemp (2012) raise the issue of whether consumers understand information related to fiber claims. Food manufacturers have begun to promote the fiber content of products; “fiber” occurs in different forms, and one form may not provide the same nutritional benefits as another.…”
Section: A Conceptual Model For Product Literacymentioning
confidence: 99%
See 2 more Smart Citations